Acute Recurrent Pancreatitis in a Child with Pancreas Divisum - Ammar A. Okasha; Areeg K. Abbas; Rahaf S. Alenazi; Abdelhadi A. Okasha (Dr. Sulaiman Al Habib Medical Journal)
Acute recurrent pancreatitis (ARP) is defined as two distinct episodes of acute recurrent pancreatitis. Acute recurrent pancreatitis in children is rare, with an incidence rate of approximately one in 500000. The most common causes of acute recurrent pancreatitis in children are infection, blunt abdominal trauma, drug toxicity, biliary stones or cystolithiasis, systemic disease, anatomic anomalies, sphincter of Oddi dysfunction, and hereditary and idiopathic causes. ARP is a precursor to develop chronic pancreatitis. We report one case of ARP with pancreas divisum, which could be an important etiology for ARP.